PENGARUH EARNINGS MANAGEMENT DAN LEVEL OF DISCLOSURE TERHADAP COST OF EQUITY CAPITAL PADA PERUSAHAAN PUBLIK SEKTOR INDUSTRI REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA - Achmad Daengs; Mahjudin .; Ririn Sulistyowati (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
This study aims to test empirically the effect of earnings management and level of disclosure to the cost of equity capital in public company of industrial real estate and property sector at Indonesia Stock Exchange in 2009-2011. In this study, earnings management will be using proxy of Utami’s model, while level of disclosure is calculated based on the Botosan’s formula (1997) and calculation of cost of equity capital will be using proxy of Ohison’s model. The results of empirical testing of this study are indicating that the earnings management and level of disclosure are significantly effect to the cost of equity capital, both partially and simultaneously. This was indicated by the results oft test EM against CO EC with a value oft-test > t-table that is 5.183 > 2.011 with a sig. value oft is smaller than the value of a that is 0.000 < 0.05, which it is means that earnings management has significantly effect to the cost of equity capital in partially. It is suggested that the level of earnings management in Indonesia as expressed by Leuz et al (2003) have carefully anticipated by investors in Indonesia Stock Exchange. The results of t-test for DC to COEC is obtained the values oft-test > t-table that is 4.555 > 2.011 with a sig. value oft is smaller than the value of a that is 0.000 < 0.05, which it is means that level of disclosure has significantly effect to the cost of equity capital in partially. While the F-test results of EM and DC against COEC is obtained the value of F-test > F-table that is 17.784 > 3.191 with a sig. value of F is smaller than the value of a that is 0.000 < 0.05, which it is means that the earnings management and level of disclosure are significantly have the effect to cost of equity capital simultaneously. From the results of multiple linear regression tests it is produce that Adjusted R Square value is 0.402 or 40.2%. This is means that as many as 40.2% of the dependent variable of cost of equity capital can be explained by the independent variables, namely earnings management and level of disclosure then the remaining 59.8% is explained by factors other than the regression models. This means that the hypothesis was supported.